ACTN3: A genetic influence on muscle function and athletic performance - Mac Arthur, D. G.; North, K. N. (Exercise and Sport Sciences Reviews, 2007)
A common variant of the ACTN3 gene, R577X, results in complete deficiency of the [alpha]-actinin-3 protein in the fast skeletal muscle fibers of more than a billion humans worldwide. We review the evidence that this genetic variant is strongly associated with elite athlete status and with normal variation in human muscle strength and sprinting speed.